2019
DOI: 10.1016/j.ctrv.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling in pancreatic ductal adenocarcinoma and a pathway towards therapy individualization: A scoping review

Abstract: Context: Pancreatic cancer (PDAC) is one of the most challenging cancers to treat with modest recent improvements in survival from new systemic therapies. There is growing interest in individualized therapy underpinned by somatic and germline genomic alterations. Objective: A systematic review of data on therapies targeting somatic and germline alterations, and their downstream pathways in PDAC. Method: A systematic literature search was conducted using PRISMA guidelines to include relevant results published a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 100 publications
0
26
0
Order By: Relevance
“…For example, three recent phase 2 trials evaluated MAPK inhibitors alone or in combination with gemcitabine in locally advanced and/or metastatic PDAC, and failed to show any survival benefit [ 13 16 ]. Other efforts include 4 studies that evaluated KRAS vaccines in PDAC patients: three studies that looked at RAS peptide vaccines and one that used GI-4000, a tarmogen (targeted molecular immunogen) designed to target cells with mutant KRAS [ 17 21 ]. Furthermore, the targeted drug tipifarnib that inhibits the Ras-dependent growth of cancer cells was tested in a large phase 3 trial and a phase 1 dose escalation trial in combination with gemcitabine in advanced PDAC [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, three recent phase 2 trials evaluated MAPK inhibitors alone or in combination with gemcitabine in locally advanced and/or metastatic PDAC, and failed to show any survival benefit [ 13 16 ]. Other efforts include 4 studies that evaluated KRAS vaccines in PDAC patients: three studies that looked at RAS peptide vaccines and one that used GI-4000, a tarmogen (targeted molecular immunogen) designed to target cells with mutant KRAS [ 17 21 ]. Furthermore, the targeted drug tipifarnib that inhibits the Ras-dependent growth of cancer cells was tested in a large phase 3 trial and a phase 1 dose escalation trial in combination with gemcitabine in advanced PDAC [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, a number of important changes in the care of PDAC patients have occurred: (1) It seems that the majority of patients benefit from combination chemotherapy[64], when the patients are fit and can tolerate it; (2) The possibility that both germline and somatic mutations can predict the response to certain treatments is being investigated and might offer important routes for treatment personalization[65]; (3) Different molecular subtypes of PDAC exist with peculiar genomic and transcriptomic features and distinct clinical behavior[66]; and (4) Novel models that might help in investigating the molecular features and the chemosensitivity of the patients (avatar or organoids) almost in real time have been developed. In this scenario, the role of EUS as a tool to obtain tissue from the tumor at diagnosis in a scarcely invasive manner, possibly at multiple timepoints during the course of disease, is increasing.…”
Section: Resultsmentioning
confidence: 99%
“…An increase of 5-hmC, which is the metabolic product of 5-mC, has been described mainly in enhancers of key oncogenes such as MYC, KRAS, VEGFA, and BRD4 [44]. Therefore, 5-hmC is believed to play an important regulatory role in PDAC pathogenesis and progression [45]. Interestingly, genome-wide comprehensive methylation profiling of PDAC patient-derived xenografts (PDXs) demonstrated that PDAC stem cells (CSCs) that express high levels of DNMT1 lost the stemness phenotype upon pharmacologic or genetic DNMT1 inhibition [46].…”
Section: Dna Methylationmentioning
confidence: 99%